Academic Freedom: A Realistic Appraisal - Altbach, Philip (International Higher Education, 2009)
Problems concerning academic freedom exist almost everywherecreated by changing academic realities, political pressures, growing commercialization and marketization of higher education, or legal pressures. The purpose of this article is to argue that academic freedom needs to be carefully defined so that it can be defended in the global climate of complexity. A new, and probably more delimited, understanding of academic freedom is needed in the age of the Internet and the global knowledge economy.